Correlation of serum level of high mobility group box 1 with the burden of granulomatous inflammation in granulomatosis with polyangiitis (Wegener's). Issue 11 (16th July 2011) - Henes, F O; Chen, Y; Bley, TA; Fabel, M; Both, M; Herrmann, K; Csernok, E; Gross, WL; Moosig, F
Abstract : Objectives: To investigate the correlation of serum levels of high mobility group box 1 (HMGB1) with the extent of granulomatous inflammation in granulomatosis with polyangiitis (GPA). Methods: From 169 patients with GPA, 17 patients with granulomatous inflammation, without evidence of vasculitis were identified and 36 patients without measurable 'granuloma' formation. HMGB1 serum levels were determined and compared between the two groups, using a Mann–Whitney U test. Serum levels of 26 healthy individuals served as controls. In a further 21 patients with GPA with a pulmonary granulomatous manifestation from the study population, CT volumetry of 'granuloma' was performed. Volumes were compared with serum levels of HMGB1 (Spearman rank order test). Results: Serum levels of HMGB1 were significantly higher in patients with predominant granulomatous disease than in patients without measurable 'granuloma' manifestations (6.44±4.53 ng/ml vs 3.85±2.88 ng/ml; p=0.0107). In both groups, levels of HMGB1 were significantly higher than in controls (2.34±2.01 ng/ml; p<0.01). A positive correlation of HMGB1 serum levels with volumes of pulmonary 'granuloma' (r=0.761, p<0.0017) was seen. Conclusions: HMGB1 serum levels are significantly higher in GPA with predominant granulomatous manifestations and correlate with volumes of pulmonary 'granuloma'. HMGB1 may be used as a marker of the burden of granulomatous inflammation in GPA.